2018
DOI: 10.1159/000487162
|View full text |Cite|
|
Sign up to set email alerts
|

Hypoxia-Induced TPM2 Methylation is Associated with Chemoresistance and Poor Prognosis in Breast Cancer

Abstract: Background/Aims: Tropomyosin-2 (TPM2) plays important roles in functions of the cytoskeleton, such as cytokinesis, vesicle transport, cell proliferation, migration and apoptosis,and these functions imply that TPM2 also plays a role in cancer development. Indeed, it has been shown that TPM2 plays a critical role in some cancers. However, the role of TPM2 in breast cancer is still poorly characterized. Thus, we explored the role of TPM2 in breast cancer. Methods: We analysed TPM2 expression and its correlation w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
33
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 43 publications
(37 citation statements)
references
References 48 publications
2
33
0
2
Order By: Relevance
“…Indeed, both the mRNA expression and protein levels of this molecule have been shown to be significantly decreased in colorectal cancer compared with paired adjacent normal tissue (218). In breast cancer, the downregulated expression of this protein is due to its promoter methylation, induced by hypoxia, leading to cell invasiveness, poor prognosis and chemoresistance (219). In another independent study, Shin et al found that the loss of Tpm2.1 increased the efficiency of migration of breast cancer cells out of the spheroids on different coated extracellular matrices (220).…”
Section: Cytoskeletonmentioning
confidence: 99%
“…Indeed, both the mRNA expression and protein levels of this molecule have been shown to be significantly decreased in colorectal cancer compared with paired adjacent normal tissue (218). In breast cancer, the downregulated expression of this protein is due to its promoter methylation, induced by hypoxia, leading to cell invasiveness, poor prognosis and chemoresistance (219). In another independent study, Shin et al found that the loss of Tpm2.1 increased the efficiency of migration of breast cancer cells out of the spheroids on different coated extracellular matrices (220).…”
Section: Cytoskeletonmentioning
confidence: 99%
“…The cores of tumors are often chronically hypoxic, which is closely associated with a negative prognosis and a metastatic phenotype which is more resistant to cancer therapy [15, 16]. By targeting the hypoxic core of primary and metastatic sites, PNA may act to enhance blood flow and improve the therapeutic effects of standard chemotherapy, radiotherapy, and/or immunotherapy.…”
Section: Introductionmentioning
confidence: 99%
“…Following the analysis of the public and private datasets, the expression of TPM2 in the atherosclerotic tissues was observed to be lower than in normal tissues. TPM2 is a subtype of tropomyosin [28]. Tropomyosin (TPM), a thin filament-associated protein, and has been hypothesized to serve a crucial role in the regulation of muscle contraction [29].…”
Section: Discussionmentioning
confidence: 99%